Estética e envelhecimento: representação da imagem para mulheres envelhecentes - Castilho, Renata dos Santos (2011)
Getting started right from the biological relation and cultural relation also, with the body, such work aims in contextualizing the image issue when it comes to mention the aging according to the social representations of beauty, the possible meaning emerging from the point of view of some authors and verifying interviews performed with five women who aged and who gave a lot of value to their image. The discussion around such work allows the assessment of a social representation regarding the aging image may bring up social implications in people lives´. The description of beauty procedures performed by interviewers demonstrates that such processes are a way out on extending youth . Thus, the relation between beauty and aging is seen as something away and, probably due to the stigma becoming old brings to us. It is verified that the age representation by age group doesn´t take into account the broad meaning of becoming older. The question lies on an introduction of a more democratic way of getting old and to oversee beauty in an older person, verifying its subjectivity and specific details